2017
DOI: 10.30630/joiv.1.2.21
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Email And Twitter Classification Accuracy Based On Preprocessing Bayes Naive Classifier Optimization In Integrated Digital Assistant

Abstract: Abstract-This research focuses on improving

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Purwarianti, Andhika, Wicaksono, Afif, and Ferdian [8] proposed a processing toolkit for natural language in Indonesian that contains many natural language processing modules. A. Erianda and I. Rahmayuni [27] bring off research on how to improve the classification of Twitter and email data using naive bayes. Their research concluded that word noise can reduce the accuracy of the classification system.…”
Section: Introductionmentioning
confidence: 99%
“…Purwarianti, Andhika, Wicaksono, Afif, and Ferdian [8] proposed a processing toolkit for natural language in Indonesian that contains many natural language processing modules. A. Erianda and I. Rahmayuni [27] bring off research on how to improve the classification of Twitter and email data using naive bayes. Their research concluded that word noise can reduce the accuracy of the classification system.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of Arabic sentiment analysis on Twitter [45] or recommending not only items of interest to the user, but also the conditions are enhancing user experiences with those items [47] are also investigated. Other researchers used naïve Bayes as a text classification algorithms to improve the accuracy of email and Twitter classification [48]. Twitter more than other social networks favors the sentiment analysis due to its "public" nature and offers some APIs 1 that allow displaying the tweets of users, to get the followers and following, to search for tweets by content, etc.…”
Section: Introductionmentioning
confidence: 99%